Indonesia’s Foreign Policy Towards The Nuclear Nonproliferation Treaty (NPT) - Tigris Asyur Sipahutar (International Journal on Social Science, Economics and Art, 2020)
This study tried to decipher the facts about Indonesia's foreign policy towards the Nuclear Nonproliferation Treaty. In Indonesia the nuclear nonproliferation treaty has been signed since the beginning of the emergence of this agreement. Indonesia with the principle of free and active political uphold international security. As related to Indonesia's foreign policy, there are three alternative policies that can be taken by Indonesia to the Nuclear Nonproliferation Treaty that is being proactive by ratifying the treaty, the second is a policy alternative abstained or even a third policy alternative is a nuclear nonproliferation treaty by refusing to participate did not ratify this agreement. The theory used to explain the problems is the theory of foreign policy rational choice theory. To see more clearly that the actions or measures taken related to nuclear nonproliferation Indonesia state of rationality that is not only internationally but also think about the interests of national interest. By using literature as a primary method of data collection, this study relies on the analysis of data obtained from books, journals, magazines, newspapers and internet sites and their relevance to the theory used. Indonesia's Foreign Policy related indicators of national interests that Indoneisa always the national interest in international level. Associated with national capabilities, in this study found that Indonesia has not found the domestic political framework that is relatively permanent, which is relatively permanent when domestic politics, this is the best to build national capabilities as the basis for the implementation of free and active foreign policy that is more solid. Related to diplomacy that in the era of democratization and globalization implementation of foreign relations and diplomacy is no longer a government.